2014
DOI: 10.1155/2014/468521
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload Is Rare in Patients Homozygous for the H63D Mutation

Abstract: H63D homozygosity was associated with an elevated mean ferritin level, but only 6.7% had documented iron overload at follow-up. The penetrance of the H63D mutation appeared to be low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 23 publications
2
38
0
1
Order By: Relevance
“…Two other commonly encountered mutations of the HFE gene are H63D and S65C, which are often included in HFE genetic panels. However, patients with homozygous H63D or S65C mutations, or those with C282Y heterozygosity, do not generally develop clinically significant iron overload unless other external iron‐increasing factors are present . There remains ambiguity regarding C282Y/H63D heterozygosity and whether this can lead to overt iron overload; some studies have shown a high prevalence of increased iron levels but typically only when present with other comorbid factors including hepatic steatosis, diabetes or excess alcohol consumption .…”
Section: Genetic Testing For Hereditary Haemochromatosismentioning
confidence: 99%
See 1 more Smart Citation
“…Two other commonly encountered mutations of the HFE gene are H63D and S65C, which are often included in HFE genetic panels. However, patients with homozygous H63D or S65C mutations, or those with C282Y heterozygosity, do not generally develop clinically significant iron overload unless other external iron‐increasing factors are present . There remains ambiguity regarding C282Y/H63D heterozygosity and whether this can lead to overt iron overload; some studies have shown a high prevalence of increased iron levels but typically only when present with other comorbid factors including hepatic steatosis, diabetes or excess alcohol consumption .…”
Section: Genetic Testing For Hereditary Haemochromatosismentioning
confidence: 99%
“…Even in individuals with homozygous HFE C282Y mutations, development of clinical iron overload is rare, reported in 21–28% of men and 1·2–10% of women . Given the rarity of non‐ HFE ‐associated haemochromatosis, it is difficult to quantify the penetrance of these mutations, but some research suggests that they are similarly low . Because the penetrance of HH is low, population screening for mutations has never been routinely recommended .…”
Section: Genetic Testing For Hereditary Haemochromatosismentioning
confidence: 99%
“…C282Y homozygosity is the predominant form associated with clinical symptoms in 80 to 92% of cases (Feder et al, 1996; Hanson et al, 2001; Aguilar‐Martinez et al, 2011). H63D is unlikely to produce hemochromatosis, even in homozygotes (Beutler, 2006; Adams, 2014; Kelley et al, 2014). Compound heterozygotes, C282Y/H63D, and simple heterozygotes of either mutation carry a very low risk of HH disease (Waalen et al, 2002; Gurrin et al, 2009).…”
mentioning
confidence: 99%
“…. A study by Kelley et al on patients homozygote for H63D showed that though the mutation is associated with an elevated mean ferritin level, only 6.7% of the patients documented iron overload at follow‐up. An over view on genetics and clinical implications of HFE‐associated hereditary hemochromatosis by Emanuele et al reported that knowledge of HFE‐HH is essential so that one can identify individuals at risk and provide appropriate management of care and referral.…”
Section: Discussionmentioning
confidence: 99%